Effects of Sterculia setigera Del. Stem Bark Extract on Hematological and Biochemical Parameters of Wistar Rats - Zaruwa, Moses Z. (Biochem Insights, 2016)
Africa is rich in a wide range of flora that are exploited as herbal medicines and remedies. Several diseases such as diabetes, diarrhea, dysentery and jaundice have been successfully managed using herbal medicines. Herbal decoctions or concoctions have been used as pain killers, antibiotics, and hematinics. This study evaluated the hematopoietic and biochemical properties of the stem bark of Sterculia setigera Del. in Wistar rats. Results showed that S. setigera decoction has copiously high tannin and cardiac glycoside levels. Ingestion of the decoction by rats over a 16-day period significantly (P < 0.05) increased the body weights of rats by 22.4% in the S. setigera-treated group. Hematological profiles showed raised levels of red blood cells, hemoglobin, packed cell volume, mean corpuscular volume, mean cell hemoglobin, mean cell hemoglobin concentration, and platelets, while biochemical parameters showed lower levels of alanine aminotransferase and aspartate aminotransferase, and slight increase in albumin and TP levels. We posit that the results justify the use of the stem bark of S. setigera as a hematinic by traditional medical practitioners and show its relative safety. Further experiments are needed to evaluate its safety.